(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This study examines the historical development and transformation of Russian drama and theatrical art, tracing its evolution from Classicism to contemporary theatrical trends. The research highlights the significant artistic movements, thematic innovations, and stylistic changes that have shaped Russian theater over several centuries. Emphasis is placed on the role of theater in reflecting social values, human psychology, moral dilemmas, and cultural identity. The study also explores the impact of avant-garde experimentation, Soviet ideological influences, and modern technological and multimedia approaches on contemporary performance practices. By analyzing these developments, the research demonstrates how Russian drama has continuously adapted to social, cultural, and artistic transformations while preserving its distinct aesthetic and cultural identity. This work provides insights into the ongoing dialogue between tradition and innovation in Russian theatrical art and underscores its enduring relevance in both national and international contexts.